Effectiveness of Flexible Ureterorenoscopy and Laser Lithotripsy for Multiple Unilateral Intrarenal Stones Smaller Than 2 cm - Erdal Alkan; Oguz Ozkanli; Egemen Avci; Mirac Turan; M. Murad Başar; Oguz Acar; M. Derya Balbay (Advances in Urology)
Purpose. To evaluate the safety and efficacy of RIRS for the treatment of multiple unilateral intrarenal stones smaller than 20 mm. Methods. Between March 2007 and April 2013, patients with multiple intrarenal stones smaller than 20 mm were treated with RIRS and evaluated retrospectively. Each patient was evaluated for stone number, stone burden (cumulative stone length), operative time, SFRs, and complications. Results. 173 intrarenal stones in 48 patients were included. Mean age, mean number of stones per patient, mean stone burden, and mean operative time were 40.2±10.9 years (23–63), 3.6±3.0 (2–18), 22.2±8.4 mm (12–45), and 60.3±22.0 minutes (30–130), respectively. The overall SFR was 91.7%. SFRs for patients with a stone burden less and greater than 20 mm were 100% (23/23) and 84% (21/25), respectively (χ2=26.022, P<0.001). Complications occurred in six (12.5%–6/48) patients, including urinary tract infection or high-grade fever >38.5°C in three cases, prolonged hematuria in two cases, and ureteral perforation in one case, all of whom were treated conservatively. No major complications occurred. Conclusions. RIRS is an effective treatment option in patients with multiple unilateral intrarenal stones especially when the total stone burden is less than 20 mm.